Human ACE2 transgenic pigs are susceptible to SARS-CoV-2 and develop COVID-19-like disease - Long Fung Chau; Simon Lillico; Tanja Opriessnig; Rosemary Blake; Luc Tardy; Chen-Hsuin Lee; Scott Maxwell; Claire Warren; Elizabeth Thornton; Catherine L. Mclaughlin; Gerry McLachlan; Christine Tait-Burkard; et al. (Nature Communications)
Abstract Animal models that accurately reflect COVID-19 are vital for understanding mechanisms of disease and advancing development of improved vaccines and therapeutics. Pigs are increasingly recognized as valuable models for human disease due to their genetic, anatomical, physiological, and immunological similarities to humans, and they present a more ethically viable alternative to non-human primates. However, pigs are not susceptible to SARS-CoV-2 infection which limits their utility as a model. To address this, we have developed transgenic pigs expressing human ACE2 that are susceptible to SARS-CoV-2 infection. Following challenge, clinical signs consistent with COVID-19, including fever, coughing and respiratory distress were observed, with virus replication detected in the nasal turbinates, trachea and lungs up to the study endpoint, seven days post-infection. Notably, examination of tissues revealed immunopathology in the lungs consistent with histological changes observed in fatal human COVID-19 cases. This study establishes human ACE2 transgenic pigs as a large animal model that accurately reflects many aspects of COVID-19 disease.